ECUACIONES PARA EVALUAR, ESTIMAR Y PREDECIR LA EROSIÓN HÍDRICA - Silva Escobar, Óscar (Venesuelos, 2011)
Palabras clave: Abstract Soil erosion is one of the most important processes involved in land productivity decay. From several years ago, this fact has leaded to develop mathematical methods for estimating soil losses under current or hypothetical conditions. This methods are diverse in complexity and origin. This paper presents a re-view about the most important erosion formulas and equations. Also, modifications or alternatives that pretend to overcome some original restrictions of these methods are described too. In general terms, it can be concluded that it is possible to group the different equations or procedures in function of the infor-mation that they provide: a) a classification index, like the Fournier’s degradation index, b) erosion estimates, without the possibility of evaluating use and management options, like mul-tiple regression regional formulas, and c) erosion estimates, with possibilities to take into account land use an management options, like USLE and related modifications. Key words: Erosion, sediment yield, simulation models, mathematics modelsErosión, producción de sedimentos, modelos de simulación, modelos matemáticos.